Caracterização sorológica da infecção por citomegalovirus (CMV) em pacientes portadores de doenças hematológicas atendidos na Fundação Hemoam - Silva, Jean de Melo (2019)
Cytomegalovirus (CMV) is a double-stranded DNA virus that cause, among other pathologies, mononucleosis accompanied by visceromegalies and hematological abnormalities mainly in immunocompromised individuals. This virus is a worldwide distributed pathogen that affects over 90% of population in developing countries. However, studies on epidemiology, clinical manifestations and immunological profile of CMV infection are scarce, which impairs the differential diagnosis and the establishment of infection control measures. Aim: The main objective of this study was to estimate the prevalence of CMV infection in patients carrying hematological diseases, whose receive treatment at the HEMOAM foundation. Metodology: For a period of one year, 323 blood samples from patients with haematological diseases were collected. The samples were submitted to immunoenzymatic assays to verify the presence of IgG and IgM antibodies against CMV. All the individuals who decided to participate in the study were submitted to an epidemiological survey that, among other variables, evaluated the sociodemographic characteristics of the participants as well as the risk behaviors that could be associated to the increased susceptibility to CMV infection. Results: As general result, seropositivity to anti-CMV IgG was observed in 295 patients (91.3%) and IgM in 17 patients (5.3%). Leukemia was the most frequent hematological disease, with a transfusion frequency among leukemic patients of 77.77%. Of the 144 patients with some type of leukemia, 131 had a positive result for CMV infection (91%). Among the 90 patients with some type of anemia, 84 were seropositive (93%). When seroprevalence was stratified according to gender, it was observed that the seropositivity for CMV was slightly higher among women (92.1%) than among men (90.5%). Conclusion: Given that in Manaus there are a considerable number of patients with hematological diseases, this study has epidemiological importance and provides important data regarding a better understanding of the socio-demographic profile of those infected in our region, making possible to evaluate how these factors may contribute to the susceptibility to CMV infection